PENENTUAN KADAR KAFEIN DALAM KOPI INSTAN SECARA SPEKTROFOTOMETRI ULTRAVIOLET - Supartiningsih Supartiningsih; Zuhairiah Zuhairiah; Cut Masyithah Thaib; Naim Bahagia (UNIVERSITAS SARI MUTIARA INDONESIA, 2020)
Caffeine in coffee has clinically beneficial pharmacological effects, such as stimulating the central nervous system, relieving fatigue, drowsiness and also increasing concentration. However, excessive use of caffeine can cause heart palpitations and stomach upset. According to SNI 01-7152-2006, the maximum limit of caffeine in food and beverages is 150 mg/day and 50 mg/serving. The purpose of this study was to determine the level of caffeine in instant coffee circulating in supermarkets in Medan City by Ultraviolet Spectrophotometry. Determination of caffeine content was carried out by the UV Spectrophotometry method after extraction using chloroform in an alkaline environment. The caffeine concentration can be calculated from the calibration curve regression equation. The results showed that the three instant coffee samples were determined to have different levels of caffeine, namely instant coffee sample code A 5.2585 mg/gram, code sample B 4.2348 mg/gram, and code C 133564. mg/gram. When viewed from the requirements, the caffeine content in the instant coffee samples coded A and B has exceeded the portion limit of 131.4625 mg and 84,768 mg, respectively, but is still within the limits set by SNI 01-7152-2006 if consumed in one pack. per day, henceforth the code C sample does not exceed the caffeine content limit of serving, which is 26.7128 mg of caffeine.